2013
DOI: 10.1063/1.4803749
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous effect of a fairing tower and increased blade flexibility on a downwind mounted rotor

Abstract: This is a parametric study on how blade and tower loads for a prototypical downwind offshore wind turbine are affected as the tower geometry and blade properties are changed. Downwind turbines have the potential to reduce the cost of energy, as blades can be more flexible and lighter, but the tower shadow induces additional structural vibrations. In order to reduce the latter, a fairing around the tower has been introduced. The length of the fairing is varied, adjusting the rotor overhang accordingly. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
(10 reference statements)
1
15
0
Order By: Relevance
“…For example, the European UpWind project predicted that 20 MW (252‐m rotor diameter) wind turbines might be possible for off shore conditions . General Electric has released plans to build a 12‐MW off‐shore wind turbine with a rotor radius ( R ) of 110 m. However, any percent increase in annual energy production (AEP) should be ideally larger than the corresponding percent increase in capital and operational expense (CAPEX and OPEX) so that there is a net decrease of LCOE for the system . Off‐shore wind turbines have some advantages and disadvantages compared with on‐shore wind turbines.…”
Section: Extreme‐scale Load‐aligned Wind Turbinessupporting
confidence: 59%
“…For example, the European UpWind project predicted that 20 MW (252‐m rotor diameter) wind turbines might be possible for off shore conditions . General Electric has released plans to build a 12‐MW off‐shore wind turbine with a rotor radius ( R ) of 110 m. However, any percent increase in annual energy production (AEP) should be ideally larger than the corresponding percent increase in capital and operational expense (CAPEX and OPEX) so that there is a net decrease of LCOE for the system . Off‐shore wind turbines have some advantages and disadvantages compared with on‐shore wind turbines.…”
Section: Extreme‐scale Load‐aligned Wind Turbinessupporting
confidence: 59%
“…This conceptual change should target the load and mass reduction of large scale wind turbines to reduce the costs. Two-bladed downwind turbines may reduce the disadvantages of upscaling that are observed for the three-bladed upwind turbine of this study, since the downwind rotor reduces the effect of tower-clearance on rotor mass [73,74]. This, in turn, mitigates the loads.…”
Section: Challenges Of Larger Wind Turbinesmentioning
confidence: 79%
“…6 A recent study by Reiso on downwind turbines suggested that blade mass could be reduced by 20% with a corresponding 5% reduction in blade fatigue loads without sacrificing power. 7 This study found that benefits to the blades came at the expense of a 20% larger tower bottom bending moment, although no assessment was made on the corresponding impact to the tower mass or system costs. They also showed that while even more flexible blades were feasible, they led to decreases in power production.…”
Section: Introductionmentioning
confidence: 88%
“…Increased fatigue damage from the tower shadow becomes a concern, but may be alleviated through aerodynamic fairing on the tower or other means . A recent study by Reiso on downwind turbines suggested that blade mass could be reduced by 20% with a corresponding 5% reduction in blade fatigue loads without sacrificing power . This study found that benefits to the blades came at the expense of a 20% larger tower bottom bending moment, although no assessment was made on the corresponding impact to the tower mass or system costs.…”
Section: Introductionmentioning
confidence: 99%